Automobile heritage and tourism - Conlin, Michael V, Ed (Routledge advances in tourism ; 39, 2017)
"Motoring heritage encompasses a complex range of artefacts and activities. Beyond just historic vehicles which are the primary artefacts of this niche, it also includes communities of collectors and enthusiasts, private owners and public institutions and historic motoring environments; literally thousands of museums, exhibitions, and car shows throughout the world and range of paraphernalia that includes both original and replicated promotional materials, equipment and parts and guide books. Although motoring heritage has been the subject of some limited research, Motoring Heritage and Tourism is unique in comprehensively examining its scope and role within tourism. The book looks at a vast array of topics, from the experience of travel by automobile, destination development, distinct forms of accommodation associated with motoring; automobile heritage from traditional elements such as museums through to events such as vintage automobile racing, promotion and social change to provide a thorough review of the impacts of motoring heritage on tourism. A number of theories provide a framework and are analysed throughout including, tourism and cultural change, tourism and globalization; tourism and mobility, tourism and nostalgia and tourism and communities. The title takes a global and interdisciplinary view of the subject with contributions from various geographical areas by both known and emerging scholars in this area. This book adds to the industrial heritage tourism literature and will appeal to a diverse audience, and in particular those the field of cultural heritage and industrial heritage tourism and practitioners involved with the planning, restoration, and management of automobile heritage events."--